Perception of commercial advertising by generations Y and Z - Anastasiia A. Kotelnitskaia; Ashot G. Mirzoyan (Управленец)
Generations Y and Z make up a significant share of consumers, so businesses need to adapt their advertising strategies and communication methods to the characteristics of each generation. The purpose of the paper is to investigate the differences in the perception of commercial advertising by generations Y and Z. The methodological basis of the study is marketing theory and the theory of generations. Comparison of means tests, linear regression, and Lasso regression were used as research methods. The data set of the study is represented by data from a survey of 308 respondents conducted in February 2023 and designed us ing the semantic differential method. Our findings show statistically significant differences in the perception by generations Y and Z of the colour temperature of a commercial, the dynamism and volume of the music, and friendliness of the actors. Among the factors affecting the probability of purchase by both generations are the need for product, colour temperature, and high-quality commercial editing, while generation Z is influenced by the semantic component and friendliness of the actors, and generation Y – by the emotional component. Generation Y consumers are more prone to impulse buying behaviour. The factors influencing the likelihood to purchase are ranked in descending order of importance: for generation Z, these are the need for product, inter est in the plot of the commercial, attractiveness of the actors, and exclusivity of the offer; for generation Y, these are the need for product, inspiration after watching, depth of meaning of the advertisement, and exclusivity of the offer. The results of the study may be useful to representatives of the marketing and advertising industry.